Is Anatomical Variations a Risk Factor for Cerebral Vasospasm in Anterior Communicating Complex Aneurysms Rupture?. Issue 3 (March 2020) - Jacquens, Alice; Shotar, Eimad; Bombled, Camille; Glémain, Benjamin; Sourour, Nader-Antoine; Nouet, Aurélien; Premat, Kevin; Lenck, Stephanie; Degos, Vincent; Clarençon, Frédéric
Abstract : Background and Purpose—: One-third of ruptured aneurysms are located on the anterior communicating complex with high prevalence of anatomic variations of this arterial segment. In this study, we hypothesized that anatomic variations of the anterior communicating complex increase the risk of angiographic vasospasm. Methods—: Retrospective study of prospectively collected data from a monocentric subarachnoid hemorrhage cohort of patients admitted to neurointensive care between 2002 and 2018. Univariate followed by multivariate logistic regression analysis was used to identify factors associated with angiographic vasospasm. Results—: One thousand three hundred seventy-four patients with aneurismal subarachnoid hemorrhage were admitted to our institution; 29.8% (n=410) were related to an anterior communicating complex aneurysm rupture; 9.2% (n=38) of them showed an anterior communicating artery variation. Angiographic vasospasm was diagnosed in 55.6% of this subgroup (vs 28.1%, P =0.003). In the multivariate analysis, external ventricular drain (2.2 [1.32–3.65], P =0.003) and anterior communicating artery variation (2.40 [1.2–4.9], P =0.04) were independently and significantly associated with angiographic vasospasm, while age above 60 years (0.3 [0.2–0.7]; P =0.002) was a protective factor. However, anterior communicating artery variation was not statistically associated with ischemic vasospasm or poor neurological outcome after anterior communicating artery aneurysm rupture. Conclusions—: Anatomic variation of anterior communicating artery could be a new biomarker to identify patients at risk to develop angiographic vasospasm post-subarachnoid hemorrhage. External validation cohorts are necessary to confirm these results. Abstract : Supplemental Digital Content is available in the text.